Caracterización fisicoquímico y espectrometría ultravioleta visible de la isoflavona aislado de Swartzia simplex y su similitud filogenética con biochanina A - Garcia Rengifo, Katherine (2022)
Isoflavones are a subject of study due to their great bioactive properties in human health, within this group is biochanin A, which behaves as a unique phytoestrogen due to its estrogenic conformation similar to these; but also, because it shows cardiovascular protection due to its hypocholesterolemic effects. The objective of the study was to isolate nd characterize the isoflavone from the heartwood of Swartzia simplex from a sample of this species that is phylogenetically related to S. polyphylla collected at the "El Huayo" Arboretum of the Faculty of Forestry Engineering of the UNAP, located between the Zungarococha and Nina Rumi hamlets, District of San Juan Bautista, Province of Maynas, Loreto Region. The purified product was identified and characterized by determining its physicochemical and UV-visible spectrometric parameters. The results were as follows: Melting point 216 °C, Rf value in TLC run in 2% Methanol solution: 98% dichloromethane was 50, Molecular Weight 284.262 g/mol and wavelengths of maximum absorption in methanol were sh 261.330 nm and in sodium acetate methanol it was 272.327 nm. These results are similar to those shown in the literature for biochanin A.